Design of 5GHz aperture coupled multilayer microstrip patch antenna with LTCC technology / Nur Fattahiah Haslahuddin - Haslahuddin, Nur Fattahiah (2013)
A compact aperture coupled multilayer microstrip patch antenna for WLAN application is presented in this project. In this work, transmission line model is used to simulate an aperture coupled microstrip patch antenna that designed to operate in WLAN band at 5 GHz frequency. This special feeding technique is implemented in the design to make it possible to obtain better performances and the configuration a broadband microstrip patch antenna can be realized. The goal of this thesis is to explore the dimension effects on aperture coupled antenna performance, to develop design and tuning procedure and to describe performance effects through electromagnetic principles. The specification for the proposed patch antenna is it has a frequency of 5GHz, Ferro A6S LTCC substrate, an epsilon 5.9, a substrate thickness of 0.096mm and copper thickness of 0.01mm. The simulation was done using CST Microwave Studio 2011 software. Comparative study of simulated parameters like return loss, gain, directivity, bandwidth, Voltage Standing Wave Ratio and the radiation patterns for each antenna configuration were analyzed and presented in this thesis. The results were based on the 14% size reduction of the patch antenna compared to the conventional FR4 substrate.